Organopolysiloxanes and coating compositions containing organopolysiloxanes
Patent Information
- Application Number
- CN202210399582.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-04-16
- Filing Date
- 2022-04-15
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-04-15
AI Technical Summary
但是,通常被用作催化剂的有机锡系化合物具有对人体和环境的毒性的担忧,并且近年环境规章变得严格,因此已经在避免对其的使用
[0054]本发明的有机聚硅氧烷在一分子中具有烷氧基-亚甲基-硅键作为特定构成单元,二甲基甲硅烷氧基单元(D单元)作为聚二甲基甲硅烷氧基结构介由硅亚乙基结构被引入聚合物中,并且该有机聚硅氧烷具有烷氧基甲硅烷基和/或硅烷醇基;因此,该有机聚硅氧烷比起以往的有机硅树脂和有机硅烷氧基低聚物在柔性上优异,并且也在如疏水性和水滑落性的表面防垢性质上优异。
Smart Images

Figure CN115216020B_ABST
Abstract
Description
[0001] Cross-references to related applications
[0002] This non-provisional application claims priority to Japanese Patent Application No. 2021-069695, filed on April 16, 2021, pursuant to 35 U.SC §119(a), the entire contents of which are incorporated herein by reference. Technical Field
[0003] This invention relates to organopolysiloxanes and coating compositions containing organopolysiloxanes, and more specifically, to organopolysiloxanes having specific constituent units and alkoxysilyl and / or silanol groups in one molecule, and coating compositions using the organopolysiloxanes. Background Technology
[0004] Due to its superior properties in terms of water repellency, heat resistance, weather resistance, frost resistance, electrical insulation, chemical resistance, and safety to the human body, silicone resin is now widely used in various fields.
[0005] In particular, it has a composition mainly of SiO 4 / 2 Unit (Q unit) and RSiO 3 / 2 Organopolysiloxanes with a three-dimensional cross-linked structure composed of units (T units) (R being an organic group such as alkyl or phenyl) are called organosilicon resins or organosilicon alkoxy oligomers. Due to their curability, these organopolysiloxanes are widely used in coating materials, coating agents, adhesives, and other applications.
[0006] In particular, liquid organosilasiloxane oligomers with alkoxysilyl groups as crosslinking groups are used as the main agent of solvent-free coating materials that are flammable and do not contain any organic solvents harmful to the human body (Non-Patent Document 1).
[0007] Because alkoxysilyl groups undergo hydrolysis and dehydration condensation crosslinking reactions at room temperature due to moisture in the air, the alkoxysilyl groups of organosilanicotinamide oligomers containing alkoxysilyl groups can react at room temperature to form a siloxane network through blending with a curing catalyst. Such polysiloxane cured films exhibit excellent heat resistance and weather resistance, and are therefore used in a wide range of applications, from outdoor construction to electronic components.
[0008] Furthermore, although the curing reaction can occur even at room temperature, as mentioned above, organosilaneoxy oligomers can be accelerated by heating. It can be said that organosilaneoxy oligomers possess excellent coating adaptability through the appropriate introduction of a thermosetting process based on the application.
[0009] However, as mentioned above, organosilicon resins or organosilaneoxy oligomers have advantages such as good curability and high surface hardness due to their three-dimensional cross-linked structure, but they also have problems such as insufficient flexibility and bending resistance due to their high cross-linking density, and cracks appearing on the coating film over time or when external stress is applied after film formation.
[0010] To improve the flexibility and bending resistance, the following method was employed, wherein, during the synthesis of organosilicon resins or organosilane alkoxy oligomers via hydrolysis-condensation, a diorganosiloxane (R2SiO) was introduced by combining it with an organooxyalkoxysilane. 2 / 2 D-units. However, in this case, since D-units are randomly introduced into the structure, more D-units must be added to impart flexibility, and there is a problem of deterioration of the excellent curability and surface hardness that are advantages of silicone resins.
[0011] Although a method for adding silicone oil in which the molecular ends are blocked by TEOS(Si(OCH2CH3)4) has also been proposed (Non-Patent Document 1), it has poor compatibility with organosilicon resins and organosilicon alkoxy oligomers, resulting in emulsification or repulsion of the coating film.
[0012] Another method for introducing D-units into organosilaneoxy oligomers includes chemically bonding hydrogenated silanes and alkyl olefins with a platinum catalyst, etc.
[0013] This reaction is generally referred to as the hydrosilylation reaction, and it is known that this reaction can be used to introduce alkoxysilanes into linear organosilicones via silyl ethylidene structures (Patent Documents 1, 2).
[0014] Patent Document 1 discloses an organopolysiloxane that simultaneously contains: an organosilanicotin oligomer structure having an alkoxysilyl group in one molecule, and a structure derived from a silicone oil structure having a methyl / phenyl side chain. This organopolysiloxane is obtained by subjecting a silicone oil compound containing a chain structure with a hydrogenated silyl group and a D unit, and an organosilanicotin oligomer compound having an olefin and an alkoxysilyl group on its side chain, to a hydrogenation silylation reaction.
[0015] Because the organopolysiloxane in Patent Document 1 has a relatively long chain and a high molecular weight side chain methyl / phenyl silicone oil structure, it is effective when added as a crack resistance enhancer; however, when the organopolysiloxane is cured alone, its hardness is insufficient, making it difficult to use the organopolysiloxane alone in coating materials and coating agent applications.
[0016] Patent Document 2 focuses on improving tactile feel through linear silicones such as hair treatment agents, but does not mention its application as a flexible coating material.
[0017] In the organosilane alkoxy oligomers that introduce D units via the above-mentioned hydrosilylation reaction, the properties of the diorganopolysiloxane are more readily apparent because the D units are introduced locally compared to the above-mentioned random hydrolysis condensation method; however, the hydrolyticity of the alkoxysilyl moiety is reduced in the same way, thus requiring an increase in reactivity (moisture curing property).
[0018] Furthermore, to ensure sufficient reactivity (moisture curing) at room temperature, a catalyst such as an organometallic compound is generally required; in particular, the addition of organotin compounds is especially effective. However, organotin compounds, which are commonly used as catalysts, raise concerns about their toxicity to humans and the environment, and with increasingly stringent environmental regulations in recent years, their use is being avoided.
[0019] Furthermore, when organometallic catalysts such as organotin compounds are added to dealcohol-type room temperature curing compositions, poor storage stability occurs, i.e., the siloxane bonds in the main chain are cleaved (broken) by the generated alcohol, resulting in deterioration of curability or increase in viscosity over time.
[0020] Patent documents
[0021] Patent Document 1: JP-A H06-271650
[0022] Patent Document 2: WO 2004 / 091562
[0023] Non-patent literature 1: Polymeric Materials Science and Engineering, 1998, Vol. 79, 192 Summary of the Invention
[0024] The present invention was made in view of the above circumstances, and its object is to provide an organopolysiloxane that combines hardness and flexural strength, provides a cured product with excellent detergency properties such as hydrophobicity and water droplet sliding, and provides a coating composition with good rapid curing properties and excellent safety even when using amine compounds as curing catalysts.
[0025] After conducting in-depth research to address the aforementioned problems, the inventors discovered that organopolysiloxanes having an alkoxy-methylene-silyl bond as a specific constituent unit, having alkoxysilyl and / or silanol groups, and also having D units introduced as block segments via silylethyne bonds, provide cured products with excellent rapid curing properties and the ability to meet high-dimensional requirements for hardness, flexural strength, and hydrophobicity / lubricity, even when using amine compounds instead of organotin compounds as curing catalysts. Furthermore, it was found that compositions containing this compound are suitable as curable compositions for forming materials such as coating agents, thus completing this invention.
[0026] This invention provides:
[0027] 1. An organopolysiloxane having: a constituent unit having the following general formula (1), a constituent unit having the following general formula (2), and a group having the following general formula (3) that is directly bonded to a silicon atom,
[0028]
[0029] Among them, R 1 This indicates an unsubstituted or substituted alkyl group having 1 to 12 carbon atoms, or an unsubstituted or substituted aryl group having 6 to 10 carbon atoms.
[0030]
[0031] Among them, R 2 Each of these terms independently represents an unsubstituted or substituted alkyl group having 1 to 12 carbon atoms, or an unsubstituted or substituted aryl group having 6 to 10 carbon atoms, where n is independently 2 or 3, and m is an integer from 5 to 100.
[0032] R 3 O- (3)
[0033] Among them, R 3 It represents a hydrogen atom, an unsubstituted or substituted alkyl group having 1 to 10 carbon atoms, or an unsubstituted or substituted aryl group having 6 to 10 carbon atoms;
[0034] 2. The organopolysiloxane according to 1, wherein the average structure has the following formula (4),
[0035]
[0036] Among them, R 1 R 2 R 3 , n and m represent the same meaning as above, R 4 R 5 and R 6Each of them independently represents a monovalent organic group, and a, b, c, d, e, f and g represent the number of a>0, b>0, c≥0, d≥0, e≥0, f≥0 and g>0;
[0037] 3. The organopolysiloxane according to 1 or 2, wherein the average structure is the following formula (5),
[0038]
[0039] Among them, R 1 R 2 R 3 R 4 , n, m, a, b and g represent the same meaning as above, and d represents a number where d > 0;
[0040] 4. A method for manufacturing an organopolysiloxane according to any one of 1 to 3, the method comprising hydrogenating and silanizing a vinyl-containing organopolysiloxane and an organohydrogenated polysiloxane having the following general formula (8), wherein the vinyl-containing organopolysiloxane is obtained by hydrolysis and condensation to copolymerize a trialkoxysilane having the following general formula (6) and a vinylalkoxysilane having the following general formula (7),
[0041]
[0042] Among them, R 1 and R 3 This means the same as above.
[0043]
[0044] Among them, R 2 R 3 and n represent the same meaning as above,
[0045]
[0046] Among them, R 2 'm' represents the same meaning as above;
[0047] 5. A curable composition comprising (A) an organopolysiloxane according to any one of 1 to 3 and (B) a curing catalyst;
[0048] 6. The curable composition according to 5, wherein (B) the curing catalyst is an amine compound;
[0049] 7. A cured product obtained by curing the curable composition according to 5 or 6;
[0050] 8. A coating composition comprising (A) an organopolysiloxane according to any one of 1 to 3 and (B) a curing catalyst;
[0051] 9. The coating composition according to 8, wherein (B) the curing catalyst is an amine compound; and
[0052] 10. An article comprising a coating layer formed by curing a coating agent composition according to 8 or 9.
[0053] Invention Effects
[0054] The organopolysiloxane of the present invention has an alkoxy-methylene-silane bond as a specific constituent unit in one molecule, and a dimethylsiloxane unit (D unit) is introduced into the polymer as a polydimethylsiloxane structure through a silylethyne structure. The organopolysiloxane also has alkoxysilyl and / or silanol groups. Therefore, the organopolysiloxane is superior in flexibility and also superior in surface antifouling properties such as hydrophobicity and water slippage compared to conventional organosilicon resins and organosiloxane oligomers.
[0055] Furthermore, the organopolysiloxane of the present invention also provides cured products with excellent rapid curing properties and both hardness and flexural strength, even when amine compounds are used instead of organotin compounds as curing catalysts.
[0056] Compositions containing the organopolysiloxanes of the present invention having these properties can be suitable for use as curable compositions for forming materials such as coating agents. Detailed Implementation
[0057] The present invention will now be described in detail.
[0058] The organopolysiloxane according to the present invention has a constituent unit represented by the following general formula (1), a constituent unit represented by the following general formula (2), and a group represented by the following general formula (3) that is directly bonded to silicon atoms.
[0059]
[0060] R 3 O-(3)
[0061] Here, R 1 It refers to an unsubstituted or substituted alkyl group having 1 to 12 carbon atoms, preferably 1 to 3 carbon atoms, or an unsubstituted or substituted aryl group having 6 to 10 carbon atoms.
[0062] R 1 The alkyl group having 1 to 12 carbon atoms can be straight-chain, cyclic, or branched, preferably straight-chain or branched, and more preferably straight-chain alkyl.
[0063] Specific examples include methyl, ethyl, n-propyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, and n-dodecyl, with methyl, ethyl, and tert-butyl being preferred, methyl and ethyl being more preferred, and methyl being even more preferred.
[0064] Specific examples of aryl groups having 6 to 10 carbon atoms include phenyl and naphthyl, with phenyl being preferred.
[0065] In particular, from the viewpoint of curing properties and hardness, R 1 Preferably, it is an alkyl group having 1 to 3 carbon atoms.
[0066] R 2 It refers to an unsubstituted or substituted alkyl group having 1 to 12 carbon atoms, preferably 1 to 3 carbon atoms, or an unsubstituted or substituted aryl group having 6 to 10 carbon atoms.
[0067] R 2 The alkyl group having 1 to 12 carbon atoms can be straight-chain, cyclic, or branched, preferably straight-chain or cyclic, and more preferably straight-chain alkyl.
[0068] Specific examples include methyl, ethyl, n-propyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, n-cyclopentyl (cyclopentyl), n-hexyl, n-cyclohexyl (cyclohexyl), n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, and n-dodecyl, preferably methyl and ethyl, more preferably methyl.
[0069] Specific examples of aryl groups having 6 to 10 carbon atoms include phenyl and naphthyl, with phenyl being preferred.
[0070] In particular, from the perspective of imparting flexibility, hydrophobicity, and water-slip properties, R 2 Preferably, it is an alkyl group having 1 to 3 carbon atoms.
[0071] n corresponds to the introduced unit in the main structure of the siloxane resin or oligomer, examples of which include 2 and 3, preferably 2.
[0072] m is the number of units in the dimethylpolysiloxane chain, examples of which include 5 to 100, preferably 10 to 90, and more preferably 20 to 60. When m is greater than 100, there is a problem of deterioration in the reactivity of the vinylsiloxane portion of the main chain during the hydrosilylation reaction described later.
[0073] R 3 It represents a hydrogen atom, an unsubstituted or substituted alkyl group having 1 to 10 carbon atoms, or an unsubstituted or substituted aryl group having 6 to 10 carbon atoms.
[0074] R 3The alkyl group having 1 to 10 carbon atoms can be straight-chain, cyclic, or branched, more preferably straight-chain alkyl. Specific examples include methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-decyl, with methyl, ethyl, n-propyl, n-hexyl, and n-octyl being preferred, methyl and ethyl being more preferred, and methyl being even more preferred.
[0075] Specific examples of aryl groups having 6 to 10 carbon atoms include phenyl and naphthyl, with phenyl being preferred.
[0076] In particular, from the perspective of solidification, R 3 Preferably, it is a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, more preferably a hydrogen atom, methyl or ethyl.
[0077] R 1 R 2 and R 3 Some or all of the hydrogen atoms of the alkyl or aryl group can be replaced by halogen atoms such as F, Cl or Br, or by other substituents such as cyano. Specific examples of such groups include: haloalkyl, such as 3,3,3-trifluoropropyl; cyano-substituted alkyl, such as 2-cyanoethyl.
[0078] The organopolysiloxane of the present invention is not particularly limited as long as it has a constituent unit represented by general formula (1), a constituent unit represented by general formula (2), and a group represented by general formula (3) that is directly bonded to silicon atoms, and the organopolysiloxane may have a linear structure, a branched structure, or a cross-linked structure in which the organopolysiloxane skeleton is composed.
[0079] More specifically, the organopolysiloxane of the present invention preferably has an average structure represented by the following formula (4), and by using such organopolysiloxane, better rapid curing properties, hardness, flexural strength, hydrophobicity and water slippage are achieved.
[0080]
[0081] Among them, R 1 R 2 R 3 , n and m represent the same meaning as above.
[0082] Here, R 4 R 5 and R 6 Each can independently represent a monovalent organic group.
[0083] The monovalent organic group is not particularly limited, and examples include R in general formula (1). 1 Examples include alkyl groups having 1 to 12 carbon atoms and aryl groups having 6 to 10 carbon atoms.
[0084] Some or all of the hydrogen atoms of these alkyl and aryl groups can be replaced by substituents, examples of which include halogen atoms, alkenyl groups such as vinyl, glycidyl epoxy, alicyclic epoxy, thiopropylcycloyl, (meth)acryloyloxy, mercapto, iso(thio)cyanate, succinic anhydride, amino, ethylenediamino, perfluoroalkyl, and polyether groups such as polyoxyethylene, and perfluoropolyether groups.
[0085] R 4 R 5 and R 6 There can be two or more different monovalent organic groups. In this case, the content of the two or more different monovalent organic groups is arbitrary, as long as the total content of the two or more different monovalent organic groups is 1, there is no particular limitation.
[0086] For example, as R 4 The alkyl group is 0.5 and the aryl group is 0.5, as R. 5 The alkyl group is 0.2%, and the alkyl group containing glycidyl-type epoxy group is 0.8%. Thus, any of the above-mentioned monovalent organic groups can be selected, and any content can be used.
[0087] From the perspectives of rapid curing, hardness, and flexural strength, R 4 R 5 and R 6 Preferably, the alkyl group having 1 to 12 carbon atoms without substituents, the aryl group having 6 to 10 carbon atoms without substituents, the glycidyl epoxy group, the (meth)acryloyloxy group, or the mercapto group, are preferred, and more preferably, the alkyl group having 1 to 12 carbon atoms without substituents. From the viewpoint of raw material availability, more preferred examples include methyl and phenyl.
[0088] a, b, c, d, e, f, and g represent numbers where a>0, b>0, c≥0, d≥0, e≥0, f≥0, and g>0. From the viewpoints of rapid curing, hardness, flexural strength, hydrophobicity, and water slippage, numbers with 1000≥a>0, 1000≥b>0, 500≥c≥0, 1000≥d≥0, 1000≥e≥0, 100≥f≥0, and 1000≥g>0 are preferred; numbers with 500≥a>0, 500≥b>0, 100≥c≥0, 500≥d≥0, 500≥e≥0, 50≥f≥0, and 500≥g>0 are even more preferred; and numbers with 500≥a>0, 500≥b>0, c=0, 500≥d>0, e=0, f=0, and 500≥g>0 are even more preferred.
[0089] Therefore, the organopolysiloxane of the present invention preferably has an average structure as represented by the following formula (5), and by using such organopolysiloxane, better rapid curing properties, hardness, flexural strength, hydrophobicity and water slippage properties are achieved.
[0090]
[0091] Among them, R 1 R 2 R 3 R 4 , n, m, a, b and g represent the same meaning as above, and d represents a number where d>0.
[0092] The weight-average molecular weight of the organopolysiloxane of the present invention is not particularly limited, but considering that it imparts sufficient rapid curing properties, hardness, flexural strength, hydrophobicity, and water slippage to the cured product obtained by curing a curable composition containing this compound, it is preferably 1,500 to 200,000, more preferably 5,000 to 100,000, and even more preferably 10,000 to 80,000. The weight-average molecular weight of the present invention is a polystyrene conversion value obtained by gel permeation chromatography (GPC).
[0093] The organopolysiloxane of the present invention can be prepared by the following steps: by hydrolysis and dehydration condensation to copolymerize a trialkoxysilane (hereinafter referred to as trialkoxysilane (6)) represented by the following structural formula (6), a vinylalkoxysilane (hereinafter referred to as vinylalkoxysilane (7)) represented by the following structural formula (7), and various alkoxysilanes (hereinafter referred to as alkoxysilane (9), (10), (11) or (12)) and / or their partial hydrolysis condensates, as optional components, to obtain the corresponding vinyl-containing organopolysiloxane, and then subjecting the vinyl-containing organopolysiloxane and the organohydrogen polysiloxane represented by the following structural formula (8) to a hydrogenation silylation reaction.
[0094]
[0095] Si(OR 3 )4 (9) R 4 -Si(OR 3 )3 (10)
[0096] R 5 2-Si(OR 3 )2 (11) R 6 3-Si(OR 3 (12)
[0097] Among them, R 1 ~R 6, n and m represent the same meaning as above.
[0098] Specific examples of trialkoxysilanes (6) include methoxymethyltrimethoxysilane, ethoxymethyltriethoxysilane, methoxymethylmethyldimethoxysilane, ethoxymethylmethylmethyldiethoxysilane, methoxymethylethyldimethoxysilane, ethoxymethylethyldiethoxysilane, methoxymethylhexyldimethoxysilane, ethoxymethylhexyldiethoxysilane, methoxymethyloctyldimethoxysilane, ethoxymethyloctyldiethoxysilane, methoxymethylphenyldimethoxysilane, and ethoxymethylphenyldiethoxysilane. Considering the rapid curing properties, hardness, flexural strength, hydrophobicity, and water slippage properties of the obtained organopolysiloxane, methoxymethyltrimethoxysilane and ethoxymethyltriethoxysilane are preferred.
[0099] Specific examples of trialkoxysilanes (7) include vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, vinylmethyldiethoxysilane, vinylethyldimethoxysilane, vinylethyldiethoxysilane, vinylhexyldimethoxysilane, vinylhexyldiethoxysilane, vinyloctyldimethoxysilane, vinyloctyldiethoxysilane, vinylphenyldimethoxysilane, and vinylphenyldiethoxysilane. Considering the rapid curing properties, hardness, flexural strength, hydrophobicity, and water slippage properties of the obtained organopolysiloxane, as well as its market availability as a raw material, vinyltrimethoxysilane, vinyltriethoxysilane, and vinylmethyldimethoxysilane are preferred.
[0100] Specific examples of alkoxysilanes (9) as optional components include tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetraisopropoxysilane, tetrabutoxysilane and tetraoctoxysilane.
[0101] Specific examples of alkoxysilanes (10) as optional components include methyltrimethoxysilane, propyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, phenyltrimethoxysilane, naphthyltrimethoxysilane, allyltrimethoxysilane, hexenyltrimethoxysilane, octenyltrimethoxysilane, methyltriethoxysilane, propyltriethoxysilane, hexenyltriethoxysilane, octyltriethoxysilane, decyltriethoxysilane, phenyltriethoxysilane, naphthyltriethoxysilane, allyltriethoxysilane, hexenyltriethoxysilane, octenyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-Epoxycyclohexyl)ethyltriethoxysilane, 3-epoxypropoxypropyltrimethoxysilane, 3-epoxypropoxypropyltriethoxysilane, 8-epoxypropoxyoctyltrimethoxysilane, 8-epoxypropoxyoctyltriethoxysilane, p-styryltrimethoxysilane, p-styryltriethoxysilane, methacryloyloxymethyltrimethoxysilane, methacryloyloxymethyltriethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropyltriethoxysilane, 8-methacryloyloxyoctyltrimethoxysilane, 8-methacryloyloxyoctyltriethoxysilane, acryloyloxymethyltrimethoxysilane, acryloyloxymethyltriethoxysilane Alkane, 3-Acryloyloxypropyltrimethoxysilane, 3-Acryloyloxypropyltriethoxysilane, 8-Acryloyloxyoctyltrimethoxysilane, 8-Acryloyloxyoctyltriethoxysilane, N-2-(aminoethyl)-aminomethyltrimethoxysilane, N-2-(aminoethyl)-aminomethyltriethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, N-2-(aminoethyl)-8-aminooctyltrimethoxysilane, N-2-(aminoethyl)-8-aminooctyltriethoxysilane, aminomethyltrimethoxysilane, aminomethyltriethoxysilane, 3-aminopropyltrimethoxysilane 3-Aminopropyltriethoxysilane, 8-Aminooctyltrimethoxysilane, 8-Aminooctyltriethoxysilane, N-Phenylo-aminomethyltrimethoxysilane, N-Phenylo-aminomethyltriethoxysilane, N-Phenylo-3-Aminopropyltrimethoxysilane, N-Phenylo-3-Aminopropyltriethoxysilane, N-Phenylo-8-Aminooctyltrimethoxysilane, N-Phenylo-8-Aminooctyltriethoxysilane, 3-Isocyanopropyltrimethoxysilane, 3-Isocyanopropyltriethoxysilane, Mercaptomethyltrimethoxysilane, Mercaptomethyltriethoxysilane, 3-Mercaptopropyltrimethoxysilane, 3-Mercaptopropyltriethoxysilane, 8-Mercaptooctyltrimethoxysilane 8-Mercaptooctyltriethoxysilane, 3-trimethoxysilylpropylsuccinic anhydride, 3-triethoxysilylpropylsuccinic anhydride, chloromethyltrimethoxysilane, chloromethyltriethoxysilane, 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane, 8-chlorooctyltrimethoxysilane, 8-chlorooctyltriethoxysilane, trifluoropropyltrimethoxysilane, nonafluorohexyltrimethoxysilane, tris(decafluorooctyl)trimethoxysilane, polyethylene glycol methyl-3-trimethoxysilylpropyl ether, polyethylene glycol methyl-3-triethoxysilylpropyl ether, polyethylene glycol methyl-3-trimethoxysilylpropyl ether, and polyethylene glycol methyl-3-triethoxysilylpropyl ether.
[0102] Among them, the preferred alkoxysilanes (10) are methyltrimethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, 3-epoxypropoxypropyltrimethoxysilane, 3-epoxypropoxypropyltriethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-acryloyloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, nonafluorohexyltrimethoxysilane, tris(decafluorooctyl)trimethoxysilane, and polyethylene glycol methyl-3-trimethoxysilylpropyl ether, and more preferably methyltrimethoxysilane and methyltriethoxysilane.
[0103] Specific examples of alkoxysilanes (11) as optional components include dimethyldimethoxysilane, dimethyldiethoxysilane, methylphenyldimethoxysilane, methylphenyldiethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, octenylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, 3-epoxypropoxypropylmethyldimethoxysilane, 3-epoxypropoxypropylmethyldiethoxysilane, 3-methacryloyloxypropylmethyldimethoxysilane, 3 -Methacryloxypropylmethyldiethoxysilane, 3-acryloyloxypropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, 3-chloropropylmethyldimethoxysilane, and 3-chloropropylmethyldiethoxysilane.
[0104] Among them, as alkoxysilane (11), dimethyldimethoxysilane, dimethyldiethoxysilane, diphenyldimethoxysilane, 3-epoxypropoxypropylmethyldimethoxysilane and 3-epoxypropoxypropylmethyldiethoxysilane are preferred, and dimethyldimethoxysilane and dimethyldiethoxysilane are more preferred.
[0105] Specific examples of alkoxysilanes (12) as optional components include trimethylmethoxysilane, trimethylethoxysilane, vinyldimethylmethoxysilane, 3-methacryloyloxypropyldimethylmethoxysilane, 3-methacryloyloxypropyldimethylethoxysilane, 3-acryloyloxypropyldimethylmethoxysilane, 3-acryloyloxypropyldimethylethoxysilane, N-2-(aminoethyl)-3-aminopropyldimethylmethoxysilane, and N-2-(aminoethyl)-3-aminopropyldimethylethoxysilane, preferably trimethylmethoxysilane.
[0106] Specific examples of organohydrogen polysiloxanes (8) include organohydrogen polysiloxanes in which the average number of dimethylsiloxy units m is 8, 20, 40, 60 or 90. Among them, from the viewpoint of imparting hydrosilanization reactivity, exhibiting hydrophobicity, water slippage and coating flexibility, m is preferably 20 or 40.
[0107] Although the copolymerization of the trialkoxysilanes (6) and (7) by hydrolysis and dehydration condensation with alkoxysilanes (9) to (12) as optional components is usually carried out in a solvent-free environment, the copolymerization can also be carried out in the presence of organic solvents (e.g., methanol, ethanol, isopropanol, butanol, diacetone alcohol, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, acetone, toluene, and xylene) that dissolve all the alkoxysilanes used in the reaction.
[0108] When using an organic solvent, there is no particular limitation on the amount used. Generally, it is preferred to be 20 parts by mass or less, more preferably 0.1 to 10 parts by mass, and even more preferably 0.5 to 5 parts by mass, relative to the total mass of the trialkoxysilanes (6) and (7) and the alkoxysilanes (9) to (12) as optional components.
[0109] The copolymerization via hydrolysis and dehydration condensation is carried out by adding or introducing an acid or base, which acts as a catalyst for the hydrolysis reaction, into a mixed solution or solution of the above-mentioned alkoxysilanes. In this case, the acid or base can be added dropwise to the aqueous solution.
[0110] The acid is not particularly limited, but examples of acids include hydrochloric acid, sulfuric acid, nitric acid, acetic acid, formic acid, phosphoric acid, p-toluenesulfonic acid and its hydrate, methanesulfonic acid, trifluoromethanesulfonic acid, and cation exchange resins. Hydrochloric acid, methanesulfonic acid, and cation exchange resins are preferred, hydrochloric acid and cation exchange resins are more preferred, and hydrochloric acid is even more preferred.
[0111] Relative to the total number of moles of the trialkoxysilanes (6) and (7) and the optional alkoxysilanes (9) to (12), the amount of acid used is generally preferred to be 0.001 to 1 mole, more preferably 0.01 to 0.2 moles.
[0112] The alkali is not particularly limited, but examples include sodium hydroxide, potassium hydroxide, lithium hydroxide, sodium acetate, potassium acetate, lithium acetate, sodium carbonate, sodium bicarbonate, sodium methoxide, sodium ethoxide, potassium methoxide, potassium ethoxide, potassium tert-butoxide, triethylamine, and anion exchange resins. Sodium hydroxide, potassium hydroxide, and sodium acetate are preferred, with sodium acetate being more preferred.
[0113] Relative to the total number of moles of the trialkoxysilanes (6) and (7) and the optional alkoxysilanes (9) to (12), the amount of the base used is generally preferred to be 0.001 to 1 mole, more preferably 0.01 to 0.2 moles.
[0114] Relative to 1 mole of the total number of moles of trialkoxysilanes (6) and (7) and alkoxysilanes (9) to (12) as optional components, the amount of water used for copolymerization by hydrolysis and condensation is generally preferred to be 0.1 to 100 moles, more preferably 0.3 to 10 moles, and even more preferably 0.5 to 2.0 moles.
[0115] The reaction temperature for copolymerization via hydrolysis and dehydration condensation is not particularly limited, but is typically 20–150°C, preferably 30–120°C, more preferably 40–100°C, and even more preferably 50–80°C. The reaction time is typically 1 hour or more, preferably 2–72 hours.
[0116] The concentration temperature of the reaction mixture is not particularly limited, but is typically 10–150°C, preferably 60–120°C. The concentration pressure is not particularly limited; concentration can be carried out under normal or reduced pressure.
[0117] The stoichiometric ratio of trialkoxysilanes (6) and (7) to alkoxysilanes (9) to (12) as optional components is not particularly limited. Considering the desired rapid curing, hardness, and flexural strength of the organopolysiloxane, preferably, the stoichiometric ratio is: relative to 1 mole of trialkoxysilane (6), alkoxysilane (7) is 0.001 to 1000 moles, alkoxysilane (9) is 0 to 1000 moles, alkoxysilane (10) is 0 to 1000 moles, alkoxysilane (11) is 0 to 1000 moles, and alkoxysilane (12) is 0 to 1000 moles; more preferably, relative to 1 mole of trialkoxysilane (6), the stoichiometric ratio is: The amounts of 1 mole of trialkoxysilane (6), alkoxysilane (7) are 0.01 to 100 moles, alkoxysilane (9) are 0 to 100 moles, alkoxysilane (10) are 0.001 to 100 moles, alkoxysilane (11) are 0 to 100 moles, and alkoxysilane (12) are 0 to 100 moles; more preferably, relative to 1 mole of trialkoxysilane (6), alkoxysilane (7) is 0.1 to 50 moles, alkoxysilane (9) is 0 moles, alkoxysilane (10) is 0.001 to 50 moles, alkoxysilane (11) is 0 moles, and alkoxysilane (12) is 0 moles;
[0118] Therefore, the organopolysiloxane of the present invention is preferably a vinyl-containing organopolysiloxane obtained by copolymerizing trialkoxysilanes (6), (7) and alkoxysilanes (10) through hydrolysis and dehydration condensation. Using the compound subsequently obtained by reacting with an organohydrogen polysiloxane (8) via hydrosilylation, even better rapid curing properties, hardness, flexural strength, hydrophobicity, and water-slip properties are observed.
[0119]
[0120] Among them, R 1 ~R 4 , n and m represent the same meaning as above.
[0121] The hydrosilylation of vinyl-containing organopolysiloxanes and organohydropolysiloxanes (8) can be carried out in a solvent system or a solvent-free system in the presence of a platinum catalyst or a rhodium catalyst.
[0122] In the reaction ratio between vinyl-containing organopolysiloxanes and organohydrogen-containing organopolysiloxanes, the number of Si-H groups in the organohydrogen-containing organopolysiloxane is preferably 0.1 to 2.0, more preferably 0.25 to 1.2, relative to one vinyl group in the vinyl-containing organopolysiloxane. If this number is too small, unreacted vinyl-containing organopolysiloxane may remain in excess, while if this number is too large, intermolecular crosslinking may occur excessively, thereby unnecessarily increasing the molecular weight and leading to deterioration of product stability.
[0123] As catalysts for the hydrosilylation reaction, known catalysts such as platinum (Pt), complexes having Pt as a central metal, or complexes having rhodium as a central metal can be used. Specific examples include alcoholic solutions of chloroplatinic acid, 1,3-divinyltetramethyldisiloxane complexes of chloroplatinic acid, compounds obtained by neutralizing such complexes, 1,3-divinyltetramethyldisiloxane complexes wherein the oxidation state of the central metal is Pt(II) or Pt(0), and Wilkinson catalysts of rhodium. Preferably, from the viewpoint of addition position selectivity, complexes wherein the oxidation state of the central metal is other than Pt(IV) are preferred, and in particular, 1,3-divinyltetramethyldisiloxane complexes having Pt(0) and Pt(II) as central metals are preferred.
[0124] The amount of catalyst used for the hydrosilylation reaction is not particularly limited as long as it exhibits a catalytic effect. It is preferably 0.000001 to 1 mol% relative to 1 mole of vinyl (i), and more preferably 0.0001 to 0.01 mol%. When the amount is less than 0.000001 mol%, it may not exhibit a sufficient catalytic effect, and when the amount is more than 1 mol%, the effect saturates, which may increase production costs and make it uneconomical.
[0125] The preferred temperature during the hydrosilylation reaction is 50–150°C, more preferably 60–130°C, and even more preferably 70–110°C. Below 50°C, the reaction rate is low, resulting in poor production efficiency. Above 150°C, it is difficult to control the addition position, leading to the formation of addition isomers. Furthermore, side reactions may occur, such as dehydrogenation reactions originating from the hydrosilylation alkyl group.
[0126] The preferred reaction time is 30 minutes to 10 hours.
[0127] Solvents can be used when performing a hydrosilylation reaction. There are no particular limitations as long as the solvent does not hinder the reaction or is reactive with the starting materials. Examples of solvents include: alcohol solvents such as methanol, ethanol, and propanol; ether solvents such as diethyl ether, dimethoxyethane, and tetrahydrofuran; polar solvents containing heterogeneous elements such as acetonitrile and dimethylformamide; aliphatic hydrocarbon solvents such as hexane and heptane; and aromatic hydrocarbon solvents such as toluene and xylene. These solvents can be used alone or in mixtures of two or more.
[0128] The kinetic viscosity of the organopolysiloxane of the present invention at 25°C is preferably 10–10000 mm⁻¹. 2 / s, more preferably 30 to 5000 mm 2 / s. When the kinetic viscosity is below 10 mm. 2 At speeds of 10000 mJ / s, the desired hydrophobicity and water slippage properties may not be observed. On the other hand, when the kinetic viscosity is higher than 10000 mJ / s... 2 At a rate of / s, the resulting polymer exhibits low storage stability and may be difficult to process.
[0129] The kinetic viscosity in this invention is the measurement value obtained using a Cannon-Fenske viscometer according to the method described in JIS Z8803:2011.
[0130] The curable composition and coating composition of the present invention (hereinafter, the two are collectively referred to as the composition) contain at least the above-described organopolysiloxane (A) and curing catalyst (B).
[0131] Since the composition of the present invention contains the organopolysiloxane of the present invention described above, when the organopolysiloxane is used to coat a solid substrate, due to the structure of the organopolysiloxane of the present invention, the curing speed, hardness, flexural strength, hydrophobicity and water slippage of the cured coating are improved compared with the use of conventional organopolysiloxanes.
[0132] The curing catalyst (B) is a component that accelerates the curing of the composition by accelerating the hydrolytic silane contained in the organopolysiloxane (A) to be hydrolyzed and condensed by moisture in the air. It is added to cure the composition efficiently.
[0133] The amount of curing catalyst (B) added is not particularly limited. Considering that the curing rate can be adjusted to a suitable range to prepare a cured film with the desired physical properties, improve the operability during coating, and further improve the economic efficiency of the accompanying addition, it is preferably 0.01 to 50 parts by mass relative to 100 parts by mass of component (A), more preferably 0.05 to 10 parts by mass, and even more preferably 0.1 to 5 parts by mass.
[0134] There are no particular limitations on the curing catalyst as long as it is used to cure general water condensation curing compositions. Specific examples include: alkyltin compounds such as dibutyltin oxide and dioctyltin oxide; alkyltin ester compounds such as dibutyltin diacetate, dibutyltin dilaurate, dibutyltin dioctanoate, dioctyltin dioctanoate, and dioctyltin ditert-tert-carbonate; titanates, titanium chelates, and their partial hydrolysates such as tetraisopropoxytitanium, tetra-n-butoxytitanium, tetra(2-ethylhexyloxy)titanium, dipropoxybis(acetylacetonate)titanium, diisopropoxybis(ethyl acetoacetate)titanium, and isopropoxyoctanedioltitanium; organometallic compounds such as cyclohexanediol... Zinc alkyl alkanoate, zinc stearate, zinc 2-ethyloctanoate, iron 2-ethylhexanoate, cobalt 2-ethylhexanoate, manganese 2-ethylhexanoate, cobalt naphthenate, aluminum hydroxide, aluminum alkoxides, aluminum acrylates, aluminum acrylates, aluminum siloxy compounds and aluminum chelates; aminoalkyl-substituted alkoxysilanes such as 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropyltriethoxysilane Silanes, N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldiethoxysilane, bis[3-(trimethoxysilyl)propyl]amine, bis[3-(triethoxysilyl)propyl]amine, N,N'-bis[3-(trimethoxysilyl)propyl]ethane-1,2-diamine, N,N'-bis[3-(triethoxysilyl)propyl]ethane-1,2-diamine and N-phenyl-3-aminopropyltrimethoxysilane; amine compounds and their salts such as hexylamine, dodecylamine phosphate and tetramethylguanidine; quaternary ammonium salts such as benzyltriethylacetate ammonium; Alkali metal lower fatty acid salts such as potassium acetate, sodium acetate and lithium oxalate; dialkyl hydroxyamines such as dimethyl hydroxyamine and diethyl hydroxyamine; silanes and siloxanes with guanidine groups such as tetramethylguanidinepropyltrimethoxysilane, tetramethylguanidinepropylmethyldimethoxysilane, tetramethylguanidinepropyltriethoxysilane, tetramethylguanidinepropylmethyldiethoxysilane and tetramethylguanidinepropyltri(trimethylsiloxy)silane; silanes and siloxanes containing phosphazene bases such as N,N,N',N',N”,N”-hexamethyl-N”'-[3-(trimethoxysilyl)propyl]-phosphoryltriamine, which can be used alone or in combination.
[0135] Among these, dioctyltin dilaurate, dioctyltin ditert-carbonate, tetraisopropoxytitanium, tetra-n-butoxytitanium, diisopropoxybis(ethyl acetoacetate)titanium, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, bis[3-(trimethoxysilyl)propyl]amine, N,N'-bis[3-(trimethoxysilyl)propyl]ethane-1,2-diamine, and tetramethylguanidinopropyltrimethoxysilane are preferred due to their superior reactivity. From the viewpoint of the curability of the composition, dioctyltin dilaurate, dioctyltin ditert-carbonate, tetra-n-butoxytitanium, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and tetramethylguanidinopropyltrimethoxysilane are more preferred. From the viewpoint of the composition being free of organotin compounds and having low toxicity, tetra-n-butoxytitanium, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and tetramethylguanidinopropyltrimethoxysilane are further preferred. From the viewpoint of the curability of the composition, tetra-n-butoxytitanium and 3-aminopropyltriethoxysilane are particularly preferred.
[0136] In order to improve workability by adjusting the viscosity of the composition of the present invention, or to adjust the curability of the composition and the hardness, flexibility, etc. of the resulting coating, one or more compounds selected from silane compounds optionally containing alkoxysilyl groups, organosilanicotinamide oligomers having alkoxysilyl and / or silanol groups in one molecule and organosilicon resins may be mixed separately with the organopolysiloxane as component (A) based on the intended use.
[0137] There are no particular limitations on silane compounds containing alkoxysilanes, but specific examples include those exemplified by alkoxysilanes (9) to (12).
[0138] Organosilanooxy oligomers having an alkoxysilyl group and / or a silanol group in one molecule are not particularly limited and can be commercially available products. Specific examples include X-40-9250, X-40-9246, X-40-9225, KR-500, KR-515, KC-89S, KR-401N, X-40-9227, KR-510, KR-9218, KR-400, X-40-2327, and KR-401 manufactured by Shin-Etsu Chemical Co., Ltd.
[0139] There are no particular limitations on the silicone resin used; it can be commercially available. Specific examples include KR-220L, KR-251, KR-112, KR-300, KR-311, KR-480, and KR-216 manufactured by Shin-Etsu Chemical Co., Ltd.
[0140] Furthermore, although the compositions of the present invention are preferably in a solvent-free form that is substantially free of organic solvents (which are often harmful to humans and flammable), solvents may be added and used from the viewpoint of their use and operability.
[0141] Here, "basically" means that the solvent contained in the composition is less than 1% by mass, and in particular, less than 0.1% by mass.
[0142] Specific examples of solvents that can be used include those that are the same organic solvents used in the preparation of organopolysiloxanes (A).
[0143] Solvents also include solvents that are not intentionally added to curing compositions and coating compositions, such as reactive solvents that cannot be completely removed by distillation under reduced pressure.
[0144] Depending on the intended use, various additives may be added to the compositions of the present invention, such as adhesion modifiers, inorganic or organic UV absorbers, light stabilizers, storage stability improvers, plasticizers, fillers, and pigments.
[0145] The composition of the present invention described above is applied to the surface of a solid substrate and cured to form a coating layer, thereby obtaining a coated solid substrate as a cured article.
[0146] There are no particular limitations on the coating method. As specific examples, the coating method may be appropriately selected from well-known techniques such as spraying, spin coating, dip coating, roller coating, brush coating, bar coating, and flow coating.
[0147] Solid substrates are not particularly limited, but specific examples include epoxy resins, phenolic resins, polycarbonates and polycarbonate blends, acrylic resins such as poly(methyl methacrylate), polyester resins such as polyethylene terephthalate, poly(butylene terephthalate), and unsaturated polyester resins, organic polymer substrates such as polyamide resins, polyimide resins, acrylonitrile-styrene copolymers, styrene-acrylonitrile-butadiene copolymers, polyvinyl chloride resins, polystyrene resins, blends of polystyrene and polyphenylene ether, cellulose acetate butyrate, and polyethylene resins; metallic substrates such as steel plates; surfaces to which coatings are applied; glass; ceramics; concrete; slate; textiles; inorganic fillers such as wood, stone, tiles, (hollow) silica, titanium dioxide, zirconium oxide, and alumina; and glass fiber products such as glass fiber, glass cloth, glass tape, glass pads, and cellophane. The material and shape of the substrate are not particularly limited, and the compositions of the present invention are particularly suitable for coating steel plates or glass.
[0148] When the composition of the present invention comes into contact with moisture in the atmosphere, the hydrolysis and condensation reaction of the organopolysiloxane (A) occurs, and the curing reaction begins. As an indicator of atmospheric moisture content, any humidity level within the RH range of 10% to 100% is acceptable; sufficient moisture in the air is adequate. However, generally, since hydrolysis occurs more rapidly at higher humidity levels, moisture may be added to the atmosphere if necessary.
[0149] The temperature and time of the curing reaction can be appropriately varied based on factors such as the substrate used, moisture concentration, catalyst concentration, and the type of hydrolyzable groups. As long as the heat resistance temperature of the substrate is not exceeded, the curing reaction time is typically from about 1 minute to 1 week.
[0150] Because the compositions of the present invention cure well even at room temperature, especially when room temperature curing is essential for field applications, the compositions exhibit excellent workability as the coated surface becomes non-sticky within minutes to hours. However, heat treatment within the heat resistance range of the substrate is acceptable.
[0151] Example
[0152] The present invention will be specifically described below using examples and comparative examples, but the present invention is not limited thereto.
[0153] In the following description, the kinetic viscosity of each product is the value measured at 25°C using a Cannon-Fenske viscometer according to the method described in JIS Z8803:2011. The molecular weight is the weight-average molecular weight of polystyrene measured using a GPC (gel permeation chromatography) instrument manufactured by Tosoh Corporation, with toluene as solvent and RI as detector.
[0154] The average structure of organopolysiloxanes was determined using a 300MHz NMR measuring device manufactured by JEOL Ltd. 1 H-NMR and 29 The integral value of the detection spectrum of Si-NMR is calculated.
[0155] The silanol hydroxyl content (parts by mass, hereinafter referred to as silanol content) of each product is quantified by the amount of methane gas generated when Grignard reagent (magnesium methyl iodide) is applied to each product.
[0156] The vinyl content (mol / 100g, hereinafter referred to as vinyl value) of each product was quantitatively obtained by reacting each product with Hanus solution, reacting the product with an aqueous solution of potassium iodide, and titrating the generated iodine with sodium thiosulfate.
[0157] [1] Synthesis of organopolysiloxanes
[0158] Synthesis example 1
[0159] Synthesis of organopolysiloxanes (1A)
[0160] In a 5L separable flask equipped with a stirrer, reflux condenser, dropping funnel, and thermometer, 1850 g (13.6 mol) of methyltrimethoxysilane, 300 g (1.8 mol) of methoxymethyltrimethoxysilane, 400 g (2.7 mol) of vinylmethyldimethoxysilane, and 0.7 g of maleic anhydride were added dropwise at 15°C with stirring, allowing the mixture to hydrolyze and condense at 70°C for 3 hours. Then, 60 g of a strongly acidic cation exchange resin (Lanxess Lewatit K 2629) was added, further hydrolyzing and condensing the mixture at 70°C for 3 hours. The resulting reaction solution was distilled off under normal pressure; after the distillate ceased to appear, the condensation reaction was accelerated at 105°C for 3 hours. Finally, the organopolysiloxane (1A) was obtained by removing the distillate under reduced pressure (90°C, 1.3 kPa) (yield: 1410 g). The obtained organopolysiloxane 1A was a colorless, transparent liquid represented by the following average structural formula, with a diameter of 62 mm. 2 The kinetic viscosity is 2700 Mw, the silanol hydroxyl content is 0.3% by mass, and the vinyl value is 0.15 mol / 100g.
[0161]
[0162] Example 1-1
[0163] Synthesis of organopolysiloxanes (1B)
[0164] In a 1L separable flask equipped with a stirrer, reflux condenser, dropping funnel, and thermometer, 200g of the organopolysiloxane (1A) obtained in Synthesis Example 1, 95g of the following hydrosiloxane (8-1) (reaction molar ratio, vinyl:Si-H group = 4:1), and 180g of toluene were added. Under stirring, a 1,3-divinyltetramethyldisiloxane complex of Pt(0) in a molar amount of 0.0004 moles relative to 1 mole of Si-H group was added at 80°C, and the mixture was hydrosilylated at 80°C for 3 hours. Afterwards, the distillate was removed by distillation under reduced pressure (90°C, 1.3 kPa) to obtain organopolysiloxane (1B) (yield: 282g). The obtained organopolysiloxane (1B) is a colorless, transparent liquid represented by the following average structural formula, with a diameter of 635 mm. 2 The kinetic viscosity is 26400 Mw, and the silanol hydroxyl content is 0.1% by mass.
[0165]
[0166] Examples 1-2
[0167] Synthesis of organopolysiloxanes (1C)
[0168] In a 1L separable flask equipped with a stirrer, reflux condenser, dropping funnel, and thermometer, 200g of the organopolysiloxane (1A) obtained in Synthesis Example 1, 45g of the following hydrosiloxane (8-2) (reaction molar ratio, vinyl:Si-H group = 4:1), and 180g of toluene were added. Under stirring, a 1,3-divinyltetramethyldisiloxane complex of Pt(0) in a molar amount of 0.0004 moles relative to 1 mole of Si-H group was added at 80°C, and the mixture was hydrosilylated at 80°C for 3 hours. Afterwards, the distillate was removed under reduced pressure (90°C, 1.3 kPa) to obtain organopolysiloxane (1C) (yield: 240g). The obtained organopolysiloxane (1C) is a colorless, transparent liquid represented by the following average structural formula, with a diameter of 341 mm. 2 The kinetic viscosity is 17800 Mw, and the silanol hydroxyl content is 0.1% by mass.
[0169]
[0170] Examples 1-3
[0171] Synthesis of organopolysiloxanes (1D)
[0172] In a 1L separable flask equipped with a stirrer, reflux condenser, dropping funnel, and thermometer, 200g of the organopolysiloxane (1A) obtained in Synthesis Example 1, 123g of the following hydrosiloxane (8-3) in a reaction molar ratio of vinyl:Si-H group = 4:1, and 180g of toluene were added. Under stirring, a 1,3-divinyltetramethyldisiloxane complex of Pt(0) in an amount of 0.0004 moles relative to 1 mole of Si-H group was added at 80°C, and the mixture was hydrosilylated at 80°C for 3 hours. Afterwards, the distillate was removed by distillation under reduced pressure (90°C, 1.3 kPa) to obtain organopolysiloxane (1D) (yield: 313g). The obtained organopolysiloxane (1D) is a colorless, transparent liquid represented by the following average structural formula, with a diameter of 1329 mm. 2 The kinetic viscosity is 34300 Mw, and the silanol hydroxyl content is 0.1% by mass.
[0173]
[0174] Examples 1-4
[0175] Synthesis of organopolysiloxanes (1E)
[0176] In a 1L separable flask equipped with a stirrer, reflux condenser, dropping funnel, and thermometer, 200g of the organopolysiloxane (1A) obtained in Synthesis Example 1, 193g of the following hydrosiloxane (8-4) in a reaction molar ratio of vinyl:Si-H group = 4:1, and 180g of toluene were added. Under stirring, a 1,3-divinyltetramethyldisiloxane complex of Pt(0) in an amount of 0.0004 moles relative to 1 mole of Si-H group was added at 80°C, and the mixture was hydrosilylated at 80°C for 3 hours. Afterwards, the distillate was removed by distillation under reduced pressure (90°C, 1.3 kPa) to obtain organopolysiloxane (1E) (yield: 385g). The obtained organopolysiloxane (1E) is a colorless, transparent liquid represented by the following average structural formula, having a diameter of 4714 mm. 2 The kinetic viscosity is 70,000 Mw, and the silanol hydroxyl content is 0.1% by mass.
[0177]
[0178] Synthesis example 2
[0179] Synthesis of organopolysiloxane (2A)
[0180] In a 1L separable flask equipped with a stirrer, reflux condenser, dropping funnel, and thermometer, 370 g (3.08 mol) of methyltrimethoxysilane, 80 g (0.54 mol) of vinylmethyldimethoxysilane, and 0.14 g of maleic anhydride were added dropwise. Under stirring, 69.4 g of deionized water was added dropwise at 15°C, and the mixture was hydrolyzed and condensed at 70°C for 3 hours. Then, 12 g of a strongly acidic cation exchange resin (Lanxess Lewatit K 2629) was added, and the mixture was further hydrolyzed and condensed at 70°C for 3 hours. The resulting reaction solution was distilled off under normal pressure. After the distillate no longer appeared, the condensation reaction was accelerated at 105°C for 3 hours. Finally, the distillate was removed by distillation under reduced pressure (90°C, 1.3 kPa) to obtain organopolysiloxane (2A) (yield: 290 g). The obtained organopolysiloxane (2A) is a colorless, transparent liquid represented by the following average structural formula, having a thickness of 66 mm. 2 The kinetic viscosity is 3100 Mw, the silanol hydroxyl content is 0% by mass, and the vinyl value is 0.15 mol / 100g.
[0181]
[0182] Comparative Example 1-1
[0183] Synthesis of organopolysiloxanes (2B)
[0184] In a 1L separable flask equipped with a stirrer, reflux condenser, dropping funnel, and thermometer, 200g of the organopolysiloxane (2A) obtained in Synthesis Example 2, 95g of the above-mentioned hydrosiloxane (8-1) (reaction molar ratio, vinyl:Si-H group = 4:1), and 180g of toluene were added. Under stirring, a 1,3-divinyltetramethyldisiloxane complex of Pt(0) in an amount of 0.0004 moles relative to 1 mole of Si-H group was added at 80°C, and the mixture was hydrosilylated at 80°C for 3 hours. Afterwards, the distillate was removed by distillation under reduced pressure (90°C, 1.3 kPa) to obtain organopolysiloxane (2B) (yield: 290g). The obtained organopolysiloxane (2B) is a colorless, transparent liquid represented by the following average structural formula, with a diameter of 191 mm. 2 The kinetic viscosity is 13000 Mw, and the silanol hydroxyl content is 0% by mass.
[0185]
[0186] [2] Coating composition
[0187] Examples 2-1 to 2-6, Comparative Examples 2-1 to 2-3, Reference Example 2-1
[0188] The organopolysiloxanes obtained in Examples 1-1 to 1-4, Comparative Examples 1-1, and Synthetic Example 1 were mixed with the curing catalyst according to the mixing amounts shown in Table 1 to prepare the coating compositions of Examples 2-1 to 2-6, Comparative Examples 2-1 to 2-3, and Reference Example 2-1.
[0189] Table 1
[0190]
[0191] KR-400: Methyl-based silicone coating agent (manufactured by Shin-Etsu Chemical Co., Ltd.)
[0192] TBT: Tetrabutyl titanate
[0193] KBE-903: 3-Aminopropyltriethoxysilane
[0194] MGPM: Tetramethylguanidinepropyltrimethoxysilane
[0195] The above-obtained coating agent compositions were applied to glass plates or polished steel plates using a rod coater No. 14 at 25°C and 50% RH in air, and then dried and cured for 1 day at 25°C and 50% RH to prepare cured films. The obtained cured films were evaluated as follows. The results are shown in Table 2.
[0196] Non-sticky time
[0197] Test pieces obtained by applying the coating agent composition to a glass plate using the above coating method were placed in air at 25°C and 50% RH, where moisture curing occurred. The time taken until the coating became non-sticky when pressed with a finger was recorded. Smaller values indicate better curing properties.
[0198] Pencil hardness
[0199] The results were shown by measuring the test piece obtained by forming a cured film on a glass plate using the above coating method, using the pencil scratch test method as described in JIS K 5600-5-4, by applying a load of 750g.
[0200] Bending resistance
[0201] According to the method described in JIS K 5600-5-1, test pieces obtained by forming a cured film on a polished steel plate using the above coating method were measured using a cylindrical mandrel (Type 1), and the results are shown.
[0202] Water repellency / lubricity
[0203] One drop (approximately 2 μl) of purified water was added to a test piece on which a cured film was formed on a polished steel plate using the above coating method. The water contact angle was measured using a contact angle meter (Drop Master DM-701, manufactured by Kyowa Interface Science Co., Ltd.) to evaluate water repellency. The desired contact angle value for water repellency is approximately 100° or higher. Furthermore, the same test piece with one drop (approximately 20 μl) of purified water was gradually tilted from a horizontal position, and the angle at which the water droplet began to flow was measured as the water slip angle to evaluate lubricity (water slippage). As an evaluation criterion, samples with a water slip angle less than 35° were rated "○", samples with a water slip angle of 35–45° were rated "△", and samples with a water slip angle greater than 45° were rated "×".
[0204] Table 2
[0205]
[0206] Examples 3-1 to 3-6, Comparative Examples 3-1 to 3-3, Reference Example 3-1
[0207] The organopolysiloxanes obtained in Examples 1-1 to 1-4, Comparative Examples 1-1, and Synthetic Example 1 were mixed with the curing catalyst according to the mixing amounts shown in Table 3 to prepare the coating compositions of Examples 3-1 to 3-6, Comparative Examples 3-1 to 3-3, and Reference Example 3-1.
[0208] Table 3
[0209]
[0210] KR-400: Methyl-based silicone coating agent (manufactured by Shin-Etsu Chemical Co., Ltd.)
[0211] TBT: Tetrabutyl titanate
[0212] MGPM: Tetramethylguanidinepropyltrimethoxysilane
[0213] DX 9740: Aluminum alkoxide compound (manufactured by Shin-Etsu Chemical Co., Ltd.)
[0214] Isopar G: An isoparaffin organic solvent (initial boiling point: 166°C, dry point: 177°C, manufactured by ExxonMobil).
[0215] The following evaluations were conducted using the coating compositions obtained above. The results are shown in Table 4.
[0216] Constructability
[0217] Add 2 ml of each of the above coating compositions to a black coating plate (material: SPCC-SD, specification: JIS-G-3141, size: 0.8mm×70mm×150mm, one side coated black with amino alkyd after chemical electrodeposition, manufactured by Asahi-Betechno). Apply a thin layer by hand using a paper towel and leave at 25°C for 5 minutes. Afterward, wipe off any excess composition with a dry microfiber cloth. If the wiping is light and even, the composition is rated "○"; if the wiping is slightly uneven or the wiping resistance is slightly heavy, the composition is rated "△"; if significant unevenness occurs or the wiping is too heavy and difficult to apply, the composition is rated "×".
[0218] Curing properties
[0219] Test pieces coated with the coating composition were prepared in the same manner as those used for workability evaluation. The test pieces were then placed at 25°C for 2 hours and cured to obtain test pieces with a cured film. When the coated surface of the obtained test piece was touched with a finger, samples with no sticky residue and exhibiting smoothness were evaluated as "○", samples with no sticky residue and not exhibiting smoothness were evaluated as "△", and samples with sticky residue were evaluated as "×".
[0220] Water repellency / lubricity
[0221] Test pieces coated with the coating composition were prepared in the same manner as those used for workability evaluation. The test pieces were further placed at 25°C for 2 hours and cured to obtain test pieces with a cured film. One drop (approximately 2 μl) of purified water was added to the obtained test piece, and the water contact angle was measured using a contact angle meter (Drop Master DM-701, manufactured by Kyowa Interface Science Co., Ltd.) to evaluate water repellency. The desired contact angle value for water repellency was approximately 100° or greater. Furthermore, the same test piece with one drop (approximately 20 μl) of purified water was gradually tilted from a horizontal position, and the angle at which the water droplet began to flow was measured as the water slip angle to evaluate lubricity (water slippage). As an evaluation criterion, samples with a water slip angle less than 35° were rated "○", samples with a water slip angle of 35–45° were rated "△", and samples with a water slip angle greater than 45° were rated "×".
[0222] abrasion resistance
[0223] Test pieces coated with the coating composition were prepared in the same manner as those used in the workability evaluation. The test pieces were further placed at 25°C for 12 hours and cured to obtain test pieces with a cured film. The abrasion resistance of the obtained test pieces with the cured film was tested using a simple abrasion testing machine (manufactured by Imoto Machinery). Specifically, a moving plate with the test piece fixed was moved back and forth once every 100 mm at a speed of 30 times per minute, and a friction object with a load of 500 g was mounted at the center and moved back and forth 400 times to induce wear. The water contact angle of the worn surface was measured in the same manner as in the water repellency / lubricity test, and the abrasion resistance was evaluated. In the abrasion resistance evaluation, samples with a water contact angle greater than 90% of the water contact angle before wear after 400 reciprocating motions were evaluated as "○", samples with a water contact angle in the range of 75% to 90% were evaluated as "△", and samples with a water contact angle less than 75% were evaluated as "×". The friction object used in the experiment was a 40mm wide, dry, clean cloth (a water-absorbing cloth made of cellulose / cotton composite fiber, ThreeBond product "ThreeBond 6644E") containing distilled water and wrapped around a 20mm diameter stainless steel cylinder. The friction object was positioned so that the axis of the cylinder was perpendicular to the direction of movement of the moving plate.
[0224] Table 4
[0225]
[0226] As shown in Tables 2 and 4, it was found that even when amine compounds were used as curing catalysts, the coating agents of organopolysiloxanes obtained in Examples 1-1 to 1-4 exhibited excellent rapid curing properties, and the resulting cured films combined hardness and flexural strength with excellent water repellency and lubricity.
[0227] On the other hand, it was found that coating agents using organopolysiloxanes that do not have the constituent units represented by general formula (1) have a long non-stick time and poor rapid curing, resulting in a curing film with poor abrasion resistance.
[0228] Furthermore, it was found that coatings obtained by using coating agents that do not have organopolysiloxanes represented by the general formula (2) have poor water repellency, lubricity, workability and abrasion resistance.
[0229] Japanese Patent Application No. 2021-069695 is incorporated herein by reference.
[0230] Although some preferred embodiments have been described, modifications and variations can be made to them based on the above teachings. Therefore, it should be understood that the invention can be practiced in ways different from those specifically described without departing from the scope of the appended claims.
Claims
1. An organopolysiloxane comprising: a constituent unit having the following general formula (1), a constituent unit having the following general formula (2), and a group having the following general formula (3) that is directly bonded to a silicon atom. in, R 1 This indicates an unsubstituted or substituted alkyl group having 1 to 12 carbon atoms, or an unsubstituted or substituted aryl group having 6 to 10 carbon atoms. Among them, R 2 Each of these terms independently represents an unsubstituted or substituted alkyl group having 1 to 12 carbon atoms, or an unsubstituted or substituted aryl group having 6 to 10 carbon atoms, where n is independently 2 or 3, and m is an integer from 5 to 100. Among them, R 3 This refers to a hydrogen atom, an unsubstituted or substituted alkyl group having 1 to 10 carbon atoms, or an unsubstituted or substituted aryl group having 6 to 10 carbon atoms. The average structure has the following formula (4). Among them, R 1 R 2 R 3 , n and m represent the same meaning as above, R 4 R 5 and R 6 Each of the following independently represents an alkyl group having 1 to 12 carbon atoms that is not substituted or is substituted with glycidyl epoxy, (meth)acryloyl epoxy or mercapto, or an aryl group having 6 to 10 carbon atoms that is not substituted or is substituted with glycidyl epoxy, (meth)acryloyl epoxy or mercapto, where a, b, c, d, e, f and g represent the numbers where a>0, b>0, c≥0, d≥0, e>0, f≥0 and g>0.
2. The organopolysiloxane according to claim 1, wherein, n is 2.
3. A method for preparing the organopolysiloxane of claim 1, the method comprising hydrogenating and silanizing a vinyl-containing organopolysiloxane and an organohydrogenated polysiloxane having the following general formula (8), wherein the vinyl-containing organopolysiloxane is obtained by hydrolysis and condensation to copolymerize a trialkoxysilane having the following general formula (6), a vinylalkoxysilane having the following general formula (7), an alkoxysilane represented by the following general formula (11), and alkoxysilanes represented by the following general formulas (9), (10), and (12) and / or their partially hydrolyzed condensates as optional components. in, R 1 R 2 R 3 R 4 R 5 R 6 , m and n represent the same meaning as above.
4. A curable composition comprising (A) the organopolysiloxane according to claim 1 and (B) a curing catalyst.
5. The curable composition according to claim 4, wherein, (B) The curing catalyst is an amine compound.
6. A cured product obtained by curing the curable composition according to claim 4 or 5.
7. A coating composition comprising (A) the organopolysiloxane according to claim 1 and (B) a curing catalyst.
8. The coating composition according to claim 7, wherein, (B) The curing catalyst is an amine compound.
9. An article comprising a coating layer formed by curing a coating agent composition according to claim 7 or 8.
Citation Information
Patent Citations
Game machine
JP2021069695A
Room-temperature-curable organopolysiloxane composition for oil seal, and automotive part
WO2020209083A1